Preparation and characterization of nickel catalyst on various support materials for the dry reforming of methane - Monroy, Teddy G. (Animo Repository, 2007)
Various support materials (MgO-ZrO2, ZrO2, MgO, SiO2 and у-A12O3 were loaded with 15% Ni by either wet or dry impregnation. These were calcined at 5000C and 8500C; and both reduced at 8500C with 10%H2-90%He by volume. Characterization was as follows: BET for surface area, pore volume, and pore size; SEM-EDX for surface morphology; XRD for bulk crystal structure; and TPD for the number of the active sites. Results showed that for most of the catalysts, the total surface area and pore volume decreased after calcination and reduction, which could have been due to sintering. Ni/SiO2 gave the highest surface area while Ni/MgO2-ZrO2 had the lowest. XRD analysis showed the formation of solid solutions after calcination, of which Ni/MgO already formed solid solutions even at the low calcination temperature of 5000C. It was observed that Ni/MgO-ZrO2 has the highest number of basic sites and lower acidic sites.